The association between metabolic parameters and evening chronotype and social jetlag in non-shift workers: A meta-analysis - Zhang, Rui; Cai, Xiaoling; Lin, Chu; Yang, Wenjia; Lv, Fang; Wu, Jing; Ji, Linong (Frontiers in Endocrinology, 2022)
Aims: The aim of the study was to evaluate the association between evening chronotype and social jetlag (SJL) with obesity, blood glucose and lipid levels in non-shift working adults. Methods: The databases of MEDLINE, EMBASE and Cochrane Reviews were searched for studies analyzing the metabolic parameters among groups of different chronotypes or SJL until Feb 2022. Weighted mean difference (WMD) and 95% confidence intervals (CI) were used to analyze the association between these parameters and chronotypes or SJL. Results: A total of 27 studies were included in this meta-analysis. Compared with morning chronotype, the participants with evening chronotype had higher body mass index (BMI) (WMD= 0.44 kg/m2, 95%CI, 0.30 to 0.57 kg/m2, p＜0.001), higher fasting blood glucose level (WMD= 5.83mg/dl, 95%CI, 3.27to 8.38 mg/dl, p＜0.001), higher total cholesterol level (WMD= 6.63mg/dl, 95%CI, 0.69 to 12.56 mg/dl, p=0.03), and lower high density lipoprotein cholesterol (HDL-C) level (WMD= -1.80mg/dl, 95%CI, -2.30 to -1.31 mg/dl, p＜0.001). Compared with the participants with small SJL, the participants with large SJL had larger waist circumference (WMD= 0.80cm, 95%CI, 0.77 to 0.83cm, p＜0.001). Conclusions: Evening chronotype and SJL were associated with obesity and unfavorable metabolic parameters of glucose and lipid metabolism.